A self-supporting high entropy oxide / graphene composite material and its preparation method and application
Through the preparation of self-supported high-entropy oxide/graphene composite materials, the problems of irregular morphology, low specific surface area and two-dimensional structure electrolyte infiltration of the sodium ion battery electrode material are solved, and efficient and stable sodium ion battery performance is achieved.
Patent Information
- Application Number
- CN202211229283.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-10-09
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2042-10-09
AI Technical Summary
The existing sodium ion battery electrode materials have irregular morphology, low specific surface area, poor electrochemical performance and two-dimensional structure electrolyte infiltration, resulting in insufficient cyclic stability and rate performance.
A self-supported high-entropy oxide/graphene composite material was used to prepare spinel-type high-entropy oxide by spray pyrolysis method, and composited with graphene to form a three-dimensional porous structure to enhance the conductivity of the material and contact with the electrolyte.
The high entropy oxide is uniformly distributed between the graphene sheets, forming a self-supported three-dimensional structure, improving the conductivity and electrochemical performance of the material, and enhancing the cycle stability and rate performance of the sodium ion battery.
Smart Images

Figure CN115911299B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of sodium ion battery materials, and in particular relates to a self-supporting high entropy oxide / graphene composite material and a preparation method and application thereof. Background Art
[0002] Under the guidance of the "dual carbon goals", the transformation of traditional fossil energy and the process of energy revolution have been significantly accelerated, and the development of clean and efficient energy storage, conversion and utilization technologies has become a current research hotspot. The migration kinetics of sodium ions are slower than those of lithium ions, which restricts the ability to charge and discharge quickly. The potential of sodium is higher than that of lithium (-2.71V vs. -3.04V relative to the standard hydrogen electrode), which will reduce the operating voltage and energy density of the battery. The sodium storage process can easily cause large volume changes in the electrode material, and even induce irreversible structural phase changes, affecting the cycle stability of the battery. These together constitute the technical difficulties of sodium-ion batteries. How to develop electrode materials that can store sodium efficiently, quickly and stably has become a current research hotspot.
[0003] Multi-component transition metal oxides - high entropy oxides (HEOs) have high configurational entropy, good ionic conductivity, and four core effects that give them the advantages of high specific capacity and excellent rate performance. They are considered to be one of the most promising new secondary battery negative electrode materials.
[0004] At present, pure HEOs materials all have certain shortcomings, which greatly limit the application research of sodium-ion batteries. The main reasons are as follows: (1) The materials prepared by traditional methods have irregular morphology and low specific surface area, which makes it impossible for the materials to fully contact with the electrolyte and store charge, thereby reducing their electrochemical performance; (2) The introduction of adhesives, conductive carbon black and other materials in the preparation process of coated electrodes will affect the authenticity of their electrochemical properties, reduce the energy density of the material, and also increase the cost of the material; (3) The electrolyte infiltration problem of the two-dimensional structure will lead to the limited release of the capacity of the material's own properties.
[0005] Therefore, the HEOs that are currently being studied the most are materials with rock salt structures. However, rock salt HEOs face the problem of inactive oxides that do not contribute to the reversible capacity.
[0006] Therefore, it is particularly necessary to study a self-supporting three-dimensional carbon structure to solve the above problems, while further increasing the conductivity of the material and achieving excellent electrochemical properties of the material. Summary of the invention
[0007] The technical problem to be solved by the present invention is to overcome the deficiencies and defects mentioned in the above background technology and provide a self-supporting high entropy oxide / graphene composite material and a preparation method and application thereof.
[0008] In order to solve the above technical problems, the technical solution proposed by the present invention is:
[0009] A self-supporting high entropy oxide / graphene composite material, wherein the high entropy oxide is uniformly distributed between graphene sheets, the high entropy oxide is a spinel structure, and its molecular formula is (FeNiMnCrCu)3O4.
[0010] The above-mentioned self-supporting high entropy oxide / graphene composite material, preferably, the high entropy oxide is a porous spherical structure, and the size of the spherical structure is 50-5000nm.
[0011] As a general inventive concept, the present invention also provides a method for preparing the above-mentioned self-supporting high entropy oxide / graphene composite material, characterized in that it comprises the following steps:
[0012] (1) preparing a mixed salt solution with equal moles of iron nitrate, nickel nitrate, manganese nitrate, chromium nitrate and copper nitrate, and then spray pyrolyzing the mixed salt solution to obtain a high entropy oxide with a molecular formula of (FeNiMnCrCu)3O4;
[0013] (2) adding graphite oxide paste to water for ultrasonic dispersion treatment, then adding the high entropy oxide, ultrasonically dispersing it uniformly, and freeze-drying the resulting mixed solution to obtain a self-supporting high entropy oxide / graphene precursor; the graphite oxide paste is purchased from Kruder Company, and its main components are 40% by mass of graphite oxide and 60% by mass of solvent water;
[0014] (3) placing the self-supporting high entropy oxide / graphene precursor in an inert atmosphere for sintering to obtain a self-supporting high entropy oxide / graphene composite material.
[0015] In the above preparation method, preferably, in step (1), the concentrations of iron nitrate, nickel nitrate, manganese nitrate, chromium nitrate and copper nitrate in the mixed salt solution are 0.005-0.5 mol / L respectively.
[0016] In the above preparation method, preferably, in step (1), the gas flow rate of the spray pyrolysis is 10-30 L / min, and the spray pyrolysis temperature is 700-1100°C.
[0017] In the above-mentioned preparation method, preferably, in step (2), the mass ratio of graphite oxide paste to high entropy oxide is 1:1-2, and the concentration of graphite oxide in the prepared mixed solution is 1-3 mg / mL.
[0018] In the above-mentioned preparation method, preferably, in step (2), the freeze-drying refers to freezing and drying in liquid nitrogen.
[0019] In the above preparation method, preferably, in step (3), the inert gas includes nitrogen; and the sintering refers to first heating to 300-400°C, keeping the temperature for 1-3 hours, and then heating to 700°C, keeping the temperature for 0.5-2 hours.
[0020] As a general inventive concept, the present invention also provides an application of the above-mentioned self-supporting high entropy oxide / graphene composite material or the self-supporting high entropy oxide / graphene composite material prepared by the above-mentioned preparation method in a sodium ion battery.
[0021] Compared with the prior art, the advantages of the present invention are:
[0022] (1) The high entropy oxide / graphene composite material of the present invention has a three-dimensional porous structure. The three-dimensional graphene structure can not only promote the conductivity of the material and increase the migration rate of electrons, but also increase the infiltration of the material with the electrolyte. The porous high entropy oxide can shorten the ion diffusion path and increase the migration rate of electrolyte ions while exerting the high entropy effect. The high entropy oxide is evenly distributed between the graphene sheets, which can effectively inhibit the reaction stress during the sodium insertion and de-sodiumization process, thereby helping to improve the cycle stability and rate performance of the sodium ion battery.
[0023] (2) The high entropy oxide / graphene composite material of the present invention can be used as a negative electrode material to prepare a sodium ion battery with high discharge specific capacity, excellent rate performance and stable cycle performance.
[0024] (3) The method for preparing high entropy oxide / graphene composite materials of the present invention is simple and reliable to operate, has good repeatability, strong operability, is environmentally friendly, and has low cost, and has broad prospects for industrial application. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is a SEM image of the self-supporting high entropy oxide / graphene composite material prepared in Example 1 of the present invention;
[0026] Figure 2 This is the XRD pattern of the self-supporting high entropy oxide / graphene composite material prepared in Example 1 of the present invention;
[0027] Figure 3 The first cycle charge and discharge curve of the button cell assembled from the self-supporting high entropy oxide / graphene composite material prepared in Example 1 of the present invention;
[0028] Figure 4 This is a cycle curve diagram of a button-type battery assembled from the self-supporting high entropy oxide / graphene composite material prepared in Example 1 of the present invention;
[0029] Figure 5This is an electron microscope image of the high entropy oxide with a porous structure prepared in Example 2 of the present invention;
[0030] Figure 6 This is a first cycle charge and discharge curve of a button-type battery assembled from the self-supporting high entropy oxide / graphene composite material prepared in Example 2 of the present invention. DETAILED DESCRIPTION
[0031] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and meticulously below in conjunction with the accompanying drawings and preferred embodiments of the specification, but the protection scope of the present invention is not limited to the following specific embodiments.
[0032] Unless otherwise defined, all the professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.
[0033] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.
[0034] Embodiment 1:
[0035] A self-supporting high entropy oxide / graphene composite material, wherein the high entropy oxide is uniformly distributed between graphene sheets, the high entropy oxide is a spinel structure, and its molecular formula is (FeNiMnCrCu)3O4. The high entropy oxide is a porous spherical structure, and the size of the spherical structure is about 200nm-1000nm.
[0036] The method for preparing the self-supporting high entropy oxide / graphene composite material of this embodiment comprises the following steps:
[0037] (1) preparing a mixed salt solution with equal moles of iron nitrate, nickel nitrate, manganese nitrate, chromium nitrate and copper nitrate, wherein the concentration of each component in the mixed salt solution is 0.00625 mol / L; then spray pyrolysis of the mixed salt solution is performed, the gas flow rate of the spray pyrolysis is 20 L / min, and the spray pyrolysis temperature is 1000° C., to obtain a high entropy oxide with a porous structure;
[0038] (2) adding graphite oxide paste to water for ultrasonic dispersion treatment, then adding high entropy oxide in a mass ratio of 1:1 to the graphite oxide paste, and continuing ultrasonic treatment for 2 hours to obtain a mixed solution, wherein the graphite oxide concentration in the mixed solution is 2 mg / mL;
[0039] (3) subjecting the mixed solution obtained in step (2) to rapid freeze-drying in liquid nitrogen to obtain a high entropy oxide / graphene composite material precursor;
[0040] (4) The high entropy oxide / graphene composite material precursor is placed in a tubular furnace in a nitrogen atmosphere for sintering. The temperature is first increased to 350°C at a heating rate of 5°C / min and the temperature is kept for 2 hours. Subsequently, the temperature is increased to 700°C at a heating rate of 10°C / min and the temperature is kept for 1 hour. The high entropy oxide / graphene composite material is then cooled to room temperature to obtain the high entropy oxide / graphene composite material.
[0041] The high entropy oxide / reduced graphene composite material prepared in this embodiment is composed of high entropy oxide uniformly wrapped between self-assembled graphene sheets to form a self-supporting three-dimensional structure. The electron microscope image is as follows: Figure 1 shown.
[0042] The XRD pattern of the high entropy oxide / graphene composite material prepared in this example is shown in FIG. Figure 2 As shown by Figure 2 By comparing the standard diffraction pattern, it can be seen that the main diffraction peaks in the high entropy oxide / graphene composite material match the CuMn2O4 (PDF#34-1400) and C peaks, indicating that the present invention successfully prepared the spinel high entropy oxide and successfully composited it with reduced graphene oxide.
[0043] The high entropy oxide / graphene composite material prepared in this example was used as the negative electrode material and assembled into a button cell with a sodium sheet. The first cycle charge and discharge performance was as follows: Figure 3 As shown, the cycle performance is Figure 4 As shown by Figure 3 It can be seen that at a constant current discharge density of 50mA / g, the battery's first charge capacity is 300.5mAh g -1 , discharge capacity 293.1mAhg -1 , Coulomb efficiency 97.5%; Figure 4 It can be seen that at a current density of 500 mA / g, the specific capacity can still be maintained at 246.3 mAh g after 200 cycles. -1 , which shows that the high entropy oxide / graphene composite material of the present invention has excellent cycle stability.
[0044] Embodiment 2:
[0045] A self-supporting high entropy oxide / graphene composite material, wherein the high entropy oxide is uniformly distributed between graphene sheets, the high entropy oxide is a spinel structure, and its molecular formula is (FeNiMnCrCu)3O4. The high entropy oxide is a porous spherical structure, and the size of the spherical structure is about 450-2000nm.
[0046] The method for preparing the self-supporting high entropy oxide / graphene composite material of this embodiment comprises the following steps:
[0047] (1) Equimolar amounts of iron nitrate, nickel nitrate, manganese nitrate, chromium nitrate and copper nitrate are prepared into a mixed salt solution, wherein the concentration of each component in the mixed salt solution is 0.0125 mol / L; the mixed salt solution is then subjected to spray pyrolysis at a gas flow rate of 25 L / min and a spray pyrolysis temperature of 1000°C to obtain a high entropy oxide with a porous structure, as shown in the electron microscope image. Figure 5 As shown;
[0048] (2) adding graphite oxide paste to water for ultrasonic dispersion treatment, then adding high entropy oxide in a mass ratio of 2:1 to the graphite oxide paste, and continuing ultrasonic treatment for 2 hours to obtain a mixed solution, wherein the graphite oxide concentration in the mixed solution is 2 mg / mL;
[0049] (3) subjecting the mixed solution obtained in step (2) to rapid freeze-drying in liquid nitrogen to obtain a high entropy oxide / graphene composite material precursor;
[0050] (4) The high entropy oxide / graphene composite material precursor is placed in a tubular furnace in a nitrogen atmosphere for sintering. The temperature is first increased to 350°C at a heating rate of 5°C / min and the temperature is kept for 2 hours. Subsequently, the temperature is increased to 700°C at a heating rate of 10°C / min and the temperature is kept for 1 hour. The high entropy oxide / graphene composite material is then cooled to room temperature to obtain the high entropy oxide / graphene composite material.
[0051] The high entropy oxide / reduced graphene composite material prepared in this embodiment is composed of high entropy oxide uniformly wrapped between self-assembled graphene sheets to form a self-supporting three-dimensional structure.
[0052] The high entropy oxide / graphene composite material prepared in this example is used as the negative electrode material and assembled into a button cell with a sodium sheet. The first cycle charge and discharge performance is as follows: Figure 6 As shown, at a constant current discharge density of 50 mA / g, the battery's first charge capacity is 239.8 mAh g -1 , discharge capacity 231.4mAhg -1 , Coulombic efficiency 96.5%.
Claims
1. A method for preparing a self-supporting high entropy oxide / graphene composite material, characterized in that: The high entropy oxide is uniformly distributed between graphene sheets, the high entropy oxide is a spinel structure, and its chemical formula is (FeNiMnCrCu)3O4. The preparation method comprises the following steps: (1) preparing a mixed salt solution of equimolar amounts of iron nitrate, nickel nitrate, manganese nitrate, chromium nitrate and copper nitrate, and then spray pyrolyzing the mixed salt solution to obtain a high entropy oxide with a chemical formula of (FeNiMnCrCu)3O4; (2) adding graphite oxide paste to water for ultrasonic dispersion treatment, then adding the high entropy oxide prepared in step (1), ultrasonically dispersing the mixture uniformly, and freeze-drying the resulting mixed solution to obtain a self-supporting high entropy oxide / graphene precursor; (3) The self-supporting high entropy oxide / graphene precursor is placed in an inert gas for sintering to obtain a self-supporting high entropy oxide / graphene composite material.
2. The preparation method according to claim 1, characterized in that In step (1), the concentrations of iron nitrate, nickel nitrate, manganese nitrate, chromium nitrate and copper nitrate in the mixed salt solution are 0.005-0.5 mol / L respectively.
3. The preparation method according to claim 1, characterized in that: In step (1), the gas flow rate of the spray pyrolysis is 10-30 L / min, and the spray pyrolysis temperature is 700-1100°C.
4. The preparation method according to claim 1, characterized in that: In step (2), the mass ratio of graphite oxide paste to high entropy oxide is 1:1-2, and the concentration of graphite oxide in the prepared mixed solution is 1-3 mg / mL.
5. The preparation method according to claim 1, characterized in that: In step (2), freeze drying refers to freezing and drying in liquid nitrogen.
6. The preparation method according to claim 1, characterized in that: In step (3), the inert gas includes nitrogen; the sintering is to first heat the temperature to 300-400°C, keep the temperature for 1-3 hours, then heat the temperature to 700°C, and keep the temperature for 0.5-2 hours.
7. The preparation method according to claim 1, characterized in that: The high entropy oxide is a porous spherical structure, and the size of the spherical structure is 50-5000 nm.
8. Use of a self-supporting high entropy oxide / graphene composite material prepared by the preparation method according to any one of claims 1 to 7 in a sodium ion battery.
Citation Information
Patent Citations
Spinel type mesoporous high-entropy oxide nanosphere with hollow structure, preparation method and application thereof
CN111333124A